Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Issues and challenges in providing services in the minority language: The experience of bilingual professionals in the health and social service network - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter explores the experience of bilingual professionals with the provision of health and social services in the official language of minority communities in Canada. Seventy-two professionals from Manitoba and eastern Ontario describe the main issues associated with language access, and the challenges with which they are faced in their day-to-day responsibilities with the active offer of these services. Professionals reported challenges such as shortage of bilingual professionals and services, and difficulty identifying clients who wish for services in the official language of the minority and finding bilingual professionals, as well as lack of organizational support to actively offer services in the minority language in health facilities. Some suggestions to better support the practice of active offer are provided. Key Words: active offer, health and social services, official language, minority communities, professionals.
Chapter 8

Enjeux et défis dans l’offre de services dans la langue de la minorité : l’expérience des professionnels bilingues dans le réseau de la santé et des services sociaux - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Le présent chapitre dévoile l’expérience de professionnels bilingues quant à l’offre de services sociaux et de santé dans la langue officielle de la minorité en contexte canadien. Soixante-douze professionnels du Manitoba et de l’Est ontarien décrivent les principaux enjeux associés à la langue et les défis auxquels ils sont confrontés quotidiennement dans l’offre active de ces services. Ces défis concernent la pénurie de professionnels et de services bilingues, la difficulté à repérer le client désirant un service dans la langue officielle de la minorité et les professionnels bilingues, ainsi que l’absence d’appui organisationnel pour faire une offre active de services dans les établissements de santé. Pour mieux soutenir l’offre de services dans la langue de la minorité, des pistes de solution sont proposées. Mots-clés : offre active, santé et services sociaux, langue officielle, contexte minoritaire, professionnels.
Chapitre 8